Analisis Modal Usaha Pedagang Pasar Tradisional dan Pengaruhnya Terhadap Pendapatan (Studi Empiris pada Pasar Alok Kabupaten Sikka) - Elvianti, Elisabeth; Mitan , Wilhelmina; Lamawitak , Paulus Libu (Jurnal Projemen UNIPA, 2026)
This study was conducted at Alok Market, Sikka Regency. The objectives of this study werw to identify the sources and utilization of traders’ business capital and to determine the influence of business capital on the income of market traders. The type of research employed was quantitative research. The population of this study consisted of traders at Alok Market, Sikka Regency. The research sample was selected using purposive sampling, with a total of 30 respondents. Data collection techniques used in this study included structured interviews (numerically based) and direct observation. The data analysis techniques applied were descriptive quantitative analysis and simple linear regression analysis. The results of the study indicated that 50-70% of business capital was obtained from traders’ own capital, while 30-45% originated from loan capital. In terms of capital utilization, 89% of the capital was used for asset investment and 80% for operational cost requirements. The findings of this study also confirmed that business capital had a significant influence on the income of traditional market traders.